Botanical art techniques : a comprehensive guide to watercolor, graphite, colored pencil, vellum, pen and ink, egg tempera, oils, printmaking, and more - Woodin, Carol; Jess, Robin A. (Timber Press, Incorporated, 2020)
The ultimate how-to guide to the essential botanical art techniques from the people who know it best, the American Society of Botanical Artists.